The State, the Market, Economic Growth and Poverty in China - DONALDSON, John A. (Institutional Knowledge at Singapore Management University, 2005)
The People’s Republic of China is often cited as an unprecedented success story as far as rural poverty is concerned. Despite recent reports of sometimes violent protests in rural areas over illicit land seizures and pollution, since implementing reforms in 1978, China has seen rural poverty rates fall from xxx to yyy, as economic growth increased zzz on average each year, according to World Bank estimates. Some have ascribed liberal policy prescriptions based on open markets and pro-market government policies as are largely responsible, even as they forwent expensive, large-scale mass welfare programs. Starting with their initial round of fundamental reform of China’s land policy, based since the mid-1960s on collective agriculture and an all-encompassing communal system, China’s leadership enhanced the role of the market in order to spur agriculture production and growth in China’s economy. They accomplished this through market reforms centered on a “Household Responsibility System,” under which local governments reallocated land to China’s peasant families through long-term leases, allowing them to sell agriculture production over set quotas on a free market based on gradually reformed prices.